Bioengineered Corneas Grafted as Alternatives to Human Donor Corneas in Three High‐Risk Patients. Issue 5 (21st May 2015) - Buznyk, Oleksiy; Pasyechnikova, Nataliya; Islam, M. Mirazul; Iakymenko, Stanislav; Fagerholm, Per; Griffith, May
Abstract: Corneas with severe pathologies have a high risk of rejection when conventionally grafted with human donor tissues. In this early observational study, we grafted bioengineered corneal implants made from recombinant human collagen and synthetic phosphorylcholine polymer into three patients for whom donor cornea transplantation carried a high risk of transplant failure. These patients suffered from corneal ulcers and recurrent erosions preoperatively. The implants provided relief from pain and discomfort, restored corneal integrity by promoting endogenous regeneration of corneal tissues, and improved vision in two of three patients. Such implants could in the future be alternatives to donor corneas for high‐risk patients, and therefore, merits further testing in a clinical trial.